The Quakers in peace and war. An account of their peace, principles and practice. With an introd. by R.M. Jones. With a new introd. [...] by E.B. Bronner (Garland, 1972)
With index. Photomechanical reprint of the ed.: London etc., Swarthmore Press etc., 1923.